Species composition and abundance of fishes in seagrass meadow ecosystem in tontayuo village and lamu village, batudaa pantai subdistrict, gorontalo regency, tomini bay area. - Novia Tumewu; Munirah Tuli; La Nane (Tomini Journal of Aquatic Science, 2022)
The objective of this research was to determine the species composition and abundance of fishes in the waters of Tontayuo Village and Lamu Village, Batudaa Pantai Subdistrict, Gorontalo Regency. This research was conducted from April to May 2022. The data collection of this research was carried out using a net with a length of 50 m, a widh of 2 m, and a mesh size of 1.5 cm drawn in the seagrass meadow, and it was replicated three times at each station, namely station I (Tontayuo Village) and station 2 (Lamu Village). The findings denoted that the highest species composition was found at station I with 34 species, while at station 2, there ware only 11 species. At the same time, the highest abundance value found at station 1 was Piotosus lineatus species, and the highest abudance at station II was Caranx melampyus species. Overall, the finding signified that the composition and abundance of fishes at station I and station II ware highly different due to the different water condition and fishing times.